Selective peptide bond formation via side chain reactivity and self-assembly of abiotic phosphates - Arti Sharma; Kun Dai; Mahesh D. Pol; Ralf Thomann; Yi Thomann; Subhra Kanti Roy; Charalampos G. Pappas (Nature Communications)
Abstract In the realm of biology, peptide bonds are formed via reactive phosphate-containing intermediates, facilitated by compartmentalized environments that ensure precise coupling and folding. Herein, we use aminoacyl phosphate esters, synthetic counterparts of biological aminoacyl adenylates, that drive selective peptide bond formation through side chain-controlled reactivity and self-assembly. This strategy results in the preferential incorporation of positively charged amino acids from mixtures containing natural and non-natural amino acids during the spontaneous formation of amide bonds in water. Conversely, aminoacyl phosphate esters that lack assembly and exhibit fast reactivity result in random peptide coupling. By introducing structural modifications to the phosphate esters (ethyl vs. phenyl) while retaining aggregation, we are able to tune the selectivity by incorporating aromatic amino acid residues. This approach enables the synthesis of sequences tailored to the specific phosphate esters, overcoming limitations posed by certain amino acid combinations. Furthermore, we demonstrate that a balance between electrostatic and aromatic stacking interactions facilitates covalent self-sorting or co-assembly during oligomerization reactions using unprotected N-terminus aminoacyl phosphate esters. These findings suggest that self-assembly of abiotic aminoacyl phosphate esters can activate a selection mechanism enabling the departure from randomness during the autonomous formation of amide bonds in water.